Pediatric Continuous Renal Replacement Therapy (PCRRT) expert committee recommendation on prescribing prolonged intermittent renal replacement therapy (PIRRT) in critically ill children. Issue 2 (18th February 2020) - Sethi, Sidharth Kumar; Mittal, Aliza; Nair, Nikhil; Bagga, Arvind; Iyenger, Arpana; Ali, Uma; Sinha, Rajiv; Agarwal, Indira; de Sousa Tavares, Marcelo; Abeyagunawardena, Asiri; Hanif, Mohammed; Shreshtha, Devender; et al.
Abstract: Introduction: Recently, prolonged intermittent renal replacement therapies (PIRRT) have emerged as cost‐effective alternatives to conventional CRRT and their use in the pediatric population has started to become more prominent. However, there is a lack of consensus guidelines on the use of PIRRT in pediatric patients in an intensive care setting. Methods: A literature search was performed on PubMed/Medline, Embase, and Google Scholar in conjunction with medical librarians from both India and the Cleveland Clinic hospital system to find relevant articles. The Pediatric Continuous Renal Replacement Therapy workgroup analyzed all articles for relevancy, proposed recommendations, and graded each recommendation for their strength of evidence. Results: Of the 60 studies eligible for review, the workgroup considered data from 37 studies to formulate guidelines for the use of PIRRT in children. The guidelines focused on the definition, indications, machines, and prescription of PIRRT. Conclusion: Although the literature on the use of PIRRT in children is limited, the current studies give credence to their benefits and these expert recommendations are a valuable first step in the continued study of PIRRT in the pediatric population.